THE EFFECT OF ABUSE OF INFORMATION TECHNOLOGY, MACHIAVELLIAN NATURE, ACADEMIC PROCRASTINATION AND STUDENT INTEGRITY ON ACADEMIC FRAUD BEHAVIOR OF ACCOUNTING STUDENTS AS PROSPECTIVE ACCOUNTANTS - Putry, Nur Anita Chandra; Agung, Yospingki Ali (Jurnal Ekonomi Balance, 2021)
This study aims to prove the influence of misuse of information technology, machiavellian nature, academic procrastination, and student integrity on the behavior of academic cheating accounting students as prospective accountants. This study used a descriptive quantitative method with primary data using a questionnaire. This study took sample students of the Accounting Study Program, Faculty of Economics, University of Sarjanawiyata Tamansiswa Yogyakarta class of 2017-2018. Sampling techniques using purposive sampling. Data collection is done by disseminating questionnaires through a google form. The number of questionnaires was processed as many as 112 questionnaires. The data was analyzed using multiple linear regression analysis. The results of this study showed that the misuse of information technology, machiavellian nature, and academic procrastination positively influenced the academic cheating behavior of accounting students as prospective accountants, while the integrity of students negatively influenced the academic cheating behavior of accounting students as prospective accountants.